Specific richness of bats in urban and peri-urban environments of Kisangani, Tshopo Province in the Democratic Republic of Congo - Moïse Akawa Bipoo; Prescott Akawa Musaba; Francine Botelanyele Kirongozi; Joel Amisa Kango; Madeleine Bikengaga Alimasi; Casimir Mololo Nebesse; Guy Crispin Tungaluna Gembu; Jean Paul Koto-Te-Nyiwa Ngbolua (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
This study focuses on bat diversity in the urban and peri-urban areas of Kisangani. It is situated within a context marked by increasing urbanization, habitat fragmentation, and heightened human pressure on forest ecosystems. The main objective was to determine species diversity and bat composition by site and habitat type, as well as to analyze their ecological preferences. Sampling was conducted at eight sites (Bawi, Botanical Garden of the Faculty of Sciences at the University of Kisangani, Imani, Maleke, Masako, Scholasticat, Yelenge, and the Kisangani Zoological Garden) covering five habitat types: cultivated fields (CC), primary forest (FP), young fallow (JJ), old fallow (JV), and human-modified environment (MA). Two capture techniques were used: mist nets and harp traps, set for 10 nights per site. The results show that 15 species across 5 families were recorded, with dominance by Pteropodidae (fruit bats), notably Epomops franqueti (39.89%), Myonycteris torquata (25%), and Megaloglossus woermanni (21.81%). Diversity is generally higher in peri-urban environments and young fallow (FF) habitats, while highly anthropized environments exhibit lower diversity and a different species composition. Jaccard similarity analysis and dendrogram analysis revealed a clear structuring of communities according to the degree of habitat disturbance. Peri-urban sites more closely resemble primary forests, while urban sites mainly harbor opportunistic and disturbance-tolerant species. The study also highlights the importance of forest fragments and urban green spaces as biodiversity refuges and underscores the need for tailored conservation strategies to preserve bat populations in Kisangani.